Cancer-associated fibroblasts and prostate cancer stem cells: crosstalk mechanisms and implications for disease progression - Chen, Haoran; Fang, Suping; Zhu, Xudong; Liu, Hao (Frontiers in Cell and Developmental Biology, 2024)
The functional heterogeneity and ecological niche of prostate cancer stem cells (PCSCs), which are major drivers of prostate cancer development and treatment resistance, have attracted considerable research attention. Cancer-associated fibroblasts (CAFs), which are crucial components of the tumor microenvironment (TME), substantially affect PCSC stemness. Additionally, CAFs promote PCSC growth and survival by releasing signaling molecules and modifying the surrounding environment.Conversely, PCSCs may affect the characteristics and behavior of CAFs by producing various molecules. This crosstalk mechanism is potentially crucial for prostate cancer progression and the development of treatment resistance. Using organoids to model the TME enables an in-depth study of CAF-PCSC interactions, providing a valuable preclinical tool to accurately evaluate potential target genes and design novel treatment strategies for prostate cancer. The objective of this review is to discuss the current research on the multilevel and multitarget regulatory mechanisms underlying CAF-PCSC interactions and crosstalk, aiming to inform therapeutic approaches that address challenges in prostate cancer treatment.